2010
DOI: 10.1158/1078-0432.ccr-09-1230
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Mast Cells and Pancreatic Cancer Cells Contributes to Pancreatic Tumor Progression

Abstract: Purpose To assess the clinical and pathological significance of mast cell infiltration in human pancreatic cancer and evaluate crosstalk between mast cells and cancer cells in vitro. Experimental Design Immunohistochemistry for tryptase was performed on 53 pancreatic cancer specimens. Mast cell counts were correlated with clinical variables and survival. Serum tryptase activity from cancer patients was compared to patients with benign pancreatic disease. In vitro, the effect of pancreatic cancer conditioned … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(149 citation statements)
references
References 26 publications
9
136
2
2
Order By: Relevance
“…28,29 Our study further provides experimental evidence that primary human MC promote colon cancer growth by stimulating production of pro-tumorigenic mediators in a bidirectional manner. Thus far, most studies in human MC-cancer interaction were using MC cell lines (LAD2 and HMC-1) 3035 with specific limitations that these cell lines are leukemia-derived (e.g. obtain a nature of cancer cells) and hardly express MC proteases or MC-specific receptors.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Our study further provides experimental evidence that primary human MC promote colon cancer growth by stimulating production of pro-tumorigenic mediators in a bidirectional manner. Thus far, most studies in human MC-cancer interaction were using MC cell lines (LAD2 and HMC-1) 3035 with specific limitations that these cell lines are leukemia-derived (e.g. obtain a nature of cancer cells) and hardly express MC proteases or MC-specific receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious roles of mast cells were identified in studies of neoplasms affecting the skin, including malignant melanoma (30,59,60), Merkel cell carcinoma (61), and primary cutaneous lymphoma (58). Increased numbers of mast cells were also found in pancreatic adenocarcinomas (62)(63)(64); squamous cell carcinomas (SCC) of the esophagus (65), mouth (66), and lip (67) (29, 30, 58-60, 62, 64-66, 71, 75), the extent of angiogenesis, as assessed by staining of microvessels (in most cases by immunohistochemistry using anti-human CD31 or CD34 antibodies), was positively correlated with the numbers of mast cells per unit area of tissue. In some of these studies, mast cells were shown to express VEGF (29,30).…”
Section: Studies Linking Mast Cells To Tumors In Humansmentioning
confidence: 99%
“…They support angiogenesis by expression of proangiogenic factors and by inhibition of ECM remodeling the MCs support tumor spread and metastasis. Tumor-associated mast cells are also regarded as potential therapeutic targets [124][125][126][127][128] and prognostic factor [129][130][131].…”
Section: Fibroblasts and Mast Cellsmentioning
confidence: 99%